Kultur uden klasse? – Klasse uden kultur? - Nielsen, Henrik Kaare (K&K - Kultur og Klasse, 2007)
Culture without Class? – Class without Culture? The article argues that it is still a plausible assumption that a crucial mutual relationship of exchange and influence exists between material life conditions and the formation of consciousness and cultural meaning, but that this relationship today is of a far more complex and differentiated nature than assumed by the classic theories about »culture and class«. Hence, contemporary social and cultural struggles are being carried out on other terms than previously. The argument is made that the class structure of the advanced capitalist countries has been subject to comprehensive changes and that the reproduction of the concrete cultural contexts of life and meaning, societally integrated and conditioned as they are, at the same time eludes conceptualisation on the basis of traditional theories of class and a priori determining patterns of development.